Intravitreal Daptomycin for Recalcitrant Postoperative Endophthalmitis - Jennifer M. Sim; Kapil G. Kapoor; Alan L. Wagner (Case Reports in Ophthalmology, 2016)
Purpose: To report the first case to our knowledge of intravitreal daptomycin used to successfully treat culture-negative vancomycin resistant to exogenous endophthalmitis. Methods: Case report with preoperative, intraoperative, and postoperative findings. Results: A 63-year-old Caucasian male underwent routine pars plana vitrectomy with epiretinal membrane peeling. He developed acute postoperative endophthalmitis, and underwent vitreous tap and injection of intravitreal vancomycin/ceftazidime/dexamethasone. Gram stain showed Gram-positive cocci, but cultures were negative. His infection subsequently proved very recalcitrant and his treatment course involved pars plana vitrectomy with anterior chamber washout and repeat injection of antibiotics, followed by repeat intravitreal vancomycin and ceftazidime. Ultimately, a second vitrectomy with intravitreal daptomycin controlled his intraocular infection. On each occasion, cultures were negative. Conclusion: This case suggests that vancomycin resistance should be considered in culture-negative postoperative endophthalmitis, and intravitreal daptomycin should be considered as an important treatment alternative. Although vancomycin resistance is fairly rare in endophthalmitis, acknowledgment of its increasing occurrence rate is critical for optimal management.